Relationship between university teachers’ emotional intelligence and instructional leadership competences: overview of the literature - Burkhanova, A. D.; Tazhina, G. O. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2020)
The concept of emotional intelligence is steadily gaining importance and is associated with the efficiency of the professional activity of a higher education teacher. The phenomenon of emotional competence includes understanding, management, analysis of one’s emotional state, self-regulation and the ability to understand the emotions of others and act on them, which in the intensive university edu-cational process determines the success of managing a student audience. The article discusses the con-cept of emotional intelligence concerning the professional competencies of modern university teachers. The quantitative investigation will inspect the University teachers’ instructional leadership competences toward their behavior and beliefs. The article displays the foundation of the investigation, determines the issues this examination endeavors to reply, and portrays professional importance of the examination. A literature review was conducted using various databases, the sources were mainly focused on the following issues: emotional intelligence, the leadership of the learning process and the relationship be-tween these two above-mentioned issues. The considered literature sources were grouped for each issue using the authors’ conclusions and analysis of the current state of knowledge of the research question. Key words: Emotional Intelligence, University teachers, Higher education, Instructiional leadership competence, Emotional competence.